Resistere al lavoro o alla propria esclusione? Un’analisi dei rapporti tra devianza, mascolinità e accesso alla formazione professionale nella Grande-Terre orientale (Kanaky-Nuova Caledonia) - Martino Miceli (Archivio Antropologico Mediterraneo)
In the mining regions of Grande-Terre, Kanaky-New Caledonia, many young people under the age of 30 turn to vocational training centers to obtain licences and certifications that are spendable on the labour market. Part of this audience comes from a complicated judicial past, marked by multiple prison sentences. Through a process of internal differentiation within the gangs of men who are reluctant to enter the wage labour force, the conditions are built for them to find a different position in the division of labour in the mine. This repositioning comes after a long resistance to the institution of education and the imperative of training, which in time turns into a struggle for a better position in the mining sector. This article intends to re-articulate the link between resistance and reproduction proposed by Paul Willis in 1977 to reflect on the relationships between crime, masculinity, ethnicity, education, and labour in the (post)colonial spaces, today at the centre of the supply of raw materials for the global energy transition.